The Impact of the Implementation of the Tujuh Kebiasaan Anak Indonesia Hebat Program on Improving the Discipline Character of Students - Siti Yuliana; Wantini Wantini; Djamaluddin Perawironegoro (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Strengthening disciplinary character is important to form students who are responsible, have self-awareness, respect others and are able to manage time well. This study aims to describe and analyze the impact of the implementation of the habituation program of seven habits of great Indonesian children on the improvement of discipline character. The research method uses a qualitative approach with the case study method, the case study was chosen because it allows the researcher to examine more deeply the implementation and impact of the program. The results of the study show that the implementation of the seven habits of great Indonesian children is realized in habituation activities, integrated in intracurricular, co-curricular and extracurricular activities. The habit of waking up in the morning has the greatest effect on improving the character of discipline supported by fast sleep and good worship practice. The improvement of discipline character is not only influenced by the program of the seven habits of Indonesian children but also influenced by other factors such as school rules and policies, school assistance, teacher examples, the role of parents and awareness and motivation sourced from students.